Performance of the muon detector A under TIBET Ⅲ array - 刘成 毕效军 陈天禄 陈文益 崔树旺 单增罗布 丁林恺 丁晓红 冯存峰 冯翰阳 冯振勇 苟全补 郭宏伟 郭义庆 何会海 侯正涛 胡海冰 胡红波 黄晶 李万杰 贾焕玉 姜龙 康明铭 乐贵明 雷文华 李爱凤 厉海金 刘金胜 刘茂元 卢红 孟宪茹 钱祥利 曲晓波 谭有恒 王辉 吴含荣 沈长铨 沈培若 薛良 杨振 袁爱芳 翟留名 张慧敏 张吉龙 张学尧 张勇 张毅 张颖 周勋秀 (Chinese physics C, 2013)
In order to observe gamma rays in the 100 TeV energy region, the 4500 m2 underground muon detector array using water Cherenkov technique is constructed, forming the TIBET Ⅲ＋MD hybrid array. Because the showers induced by primary gamma rays contain much fewer muons than those induced by primary hadrons, significant improvement of the gamma ray sensitivity for TIBET Ⅲ＋MD array is expected. In this paper, the design and performance of the MD-A detector with large Tyvek bag is reported.